ANALISIS HARGA POKOK PRODUKSI FULL COSTING DAN OPTIMALISASI WHATSAPP BUSINESS PADA UMKM - Handyka Putri Pradani; Zaenal Wafa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aimed to assist Permata Konveksi MSME in calculating the Cost of Production (COP) using the full costing method while also utilizing WhatsApp Business as a digital marketing medium. The method applied was a qualitative descriptive approach through the stages of interviews, mentoring implementation, and activity evaluation. The mentoring focused on classifying raw material costs, direct labor costs, and factory overhead costs to ensure that production cost recording became more systematic and accurate. In addition, the implementation of WhatsApp Business was carried out through the creation of a business profile, product catalog, and optimization of communication with customers. The results of the activity showed that the business owner became more capable of calculating the Cost of Production in a more structured manner and no longer relied solely on estimates in determining product selling prices. The use of WhatsApp Business also helped accelerate customer service, provide clearer product information, and support the improvement of digital promotion and marketing activities.